EFEKTIFITAS PIJAT TERHADAP KUALITAS TIDUR BAYI (0 – 1 TAHUN) DI PMB HASNA DEWI TAHUN 2020 - Berliana Irianti; Nelly Karlinah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Massage is a touch therapy that is in direct contact with the baby's body so that it provides a feeling of security and comfort for the baby. The massage that is done will increase the catecholamine hormone which triggers growth and development stimulation, increases appetite, increases body weight, improves sleep quality and stimulates the development of brain structure and function. The research objective was to determine the effectiveness of infant massage on the quality of baby sleep. This type of research is quasy experiment with the pretest posttest one group design approach. The research was conducted at PMB Hasna Dewi Pekanbaru. The population was the mother of 30 babies using total sampling. Collecting data by doing massage, observation and questionnaires. The results showed that the effectiveness of infant massage in improving sleep quality. Most of the babies slept better. The Wilcoxon statistical test shows a significant value of p value = 0.036